Polymer electrets and their applications. Issue 19 (24th December 2020) - Li, Xin; Wang, Yurui; Xu, Minxuan; Shi, Yueqin; Wang, Hemiao; Yang, Xin; Ying, Haoting; Zhang, Qi
Abstract: Polymer electrets have revealed great potential application in electromechanical devices because of the low weight, large quasi‐piezoelectric sensitivity, and excellent flexibility. For an electret, a permanent and macroscopic electric field exists on the surface, principally led by a macroscopic electrostatic charge on the surface or a net orientation of polar groups inside the object. Here, progress in the development of polymer electrets is reviewed. After a brief retrospect of the research courses and those typical polymer electrets that are classified into fluorine polymer and nonfluorine polymer, we present a survey on the charging methods, including corona, soft X‐ray, contact, thermal and monoenergetic particle beams. The latest representative applications (i.e., power harvesting, sensors, field effect transistors, and biomedicine) based on polymer electrets are also summarized. Finally, we complete this review with a discussion on perspectives and challenges in this field. Abstract : Progress in the development of polymer electrets is reviewed. After a brief retrospect of the research courses and those typical polymer electrets that are classified into fluorine polymer and non‐fluorine polymer, we present a survey on the charging methods, including corona, soft X‐ray, contact, thermal and monoenergetic particle beams. The latest representative applications (i.e. power harvesting, sensors, field effect transistors, and biomedicine) based on polymer electrets are also summarized.